Analisis Framing Entman dalam Pemberitaan Karhutla pada Kompas.com dan Cnnindonesia.com Tahun 2026 - Ayu Wardani; Dede Suprayitno (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study aims to analyze the framing of forest and land fire (karhutla) news coverage on Kompas.com and Cnnindonesia.com during the period of March–April 2026 using the framing model of Robert N. Entman. The analysis was conducted on five karhutla news articles from Kompas.com and three from Cnnindonesia.com. The results show that Kompas.com frames karhutla across several affected regions in Indonesia. In addition to presenting statistical data, Kompas.com highlights solution-oriented aspects in detail, such as the implementation of green policing, public warnings regarding karhutla disasters, and appeals to prevent land burning. However, the framing tends to be normative and less critical of underlying structural causes. In contrast, Cnnindonesia.com focuses its karhutla coverage primarily on the Riau region. The framing presented is more descriptive of events, with limited exploration of long-term (sustainable) solutions and mitigation efforts. The findings of this study indicate that the media play a strategic role in shaping public perceptions of disasters. However, they have not yet fully optimized their educational and mitigative functions in building community resilience to forest and land fire disasters.